The Mediating Effect of Perceived Organizational Support in the Relationship Between Organizational Ethical Climate and Turnover Intention: An Empirical Research in the Private Sector - KARA, Adem; AYDIN, Esra; AŞAN AZİZOĞLU, Öznur (International Journal of Contemporary Economics and Administrative Sciences, 2022)
Drawing on the social exchange theory, the present study firstly investigates the effect of the organizational ethical climate on a very critical work attitude as turnover intention. Furthermore, the mediating effect of perceived organizational support in this relationship is discovered. The sample group of the research consists of 161 private-sector employees from Ankara, Turkey. In the data analysis process, partial least squares structural equation modeling (PLS-SEM) was used. The findings revealed that organizational ethical climate had a significant negative association with turnover intention. For the mediation analysis, two different methods were used suggested by Baron and Kenny (1986) and Zhao et al. (2010). Within the scope of current research, an atypical situation that was interpreted as suppression or competitive mediation effect in the literature was encountered. However, findings indicated that perceived organizational support had a partial mediating effect on the association between organizational ethical climate and turnover intention.